2016
DOI: 10.1159/000452550
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Aqueous Extract of Salvia Miltiorrhiza Reduces Blood Pressure through Inhibition of Vascular Remodelling and Oxidative Stress in Spontaneously Hypertensive Rats

Abstract: Background/Aims: Salvia miltiorrhiza (SM) contains four major aqueous active ingredients, which have been isolated, purified and identified as danshensu (DSS), salvianolic acid A (Sal-A), salvianolic acid B (Sal-B) and protocatechuic aldehyde (PAL), totally abbreviated as SABP. Although SM is often used to treat various cardiovascular diseases in traditional Chinese medicine, the efficacy and function of optimal compatibility ratio of SM's active ingredients (SABP) in the prevention and treatment of cardiovasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 48 publications
1
24
0
Order By: Relevance
“…In previous studies we have shown that prophylactic administration of SAA slowed the progression of pulmonary vascular remodeling, and may be associated with the Smad signaling pathway 32 . More recent evidence also reveals that SAA alleviates hypertension through inhibiting oxidative stress and TGF-β signal transduction pathway 34 .…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies we have shown that prophylactic administration of SAA slowed the progression of pulmonary vascular remodeling, and may be associated with the Smad signaling pathway 32 . More recent evidence also reveals that SAA alleviates hypertension through inhibiting oxidative stress and TGF-β signal transduction pathway 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Salvia miltiorrhiza (SM), a kind of perennial herb that derived from Salvia genus of the Labiatae family, the dry roots and rhizomes are officially listed in the Chinese Pharmacopoeia [ 1 , 2 ], and it is highly valued and one of the most widely used traditional Chinese medicines (TCM) by virtue of its function to “promote blood circulation and remove blood stasis” that was firstly recorded in Shennong's Classic of Materia Medica (200–300 AD, Han Dynasty). The remarkable effects of S. miltiorrhiza on treatment of complicated cardiovascular diseases and cerebrovascular diseases have been reported during the past decades [ 3 , 4 , 5 ]. Additionally, numerous studies have demonstrated that S. miltiorrhiza possesses a wide range of pharmacological effects, including anti-oxidative, myocardial infarction, anti-fibrotic [ 6 ], anti-inflammatory [ 7 ], anti-hypertension [ 8 ] and anti-neoplastic [ 9 ] effects.…”
Section: Introductionmentioning
confidence: 99%
“…It is often used for the treatment of cardio-cerebral-vascular disease caused by blood stasis [30,44,45]. Existing studies have shown that DSS, SAA, SAB, and HSYA have the ability to scavenge free oxygen radicals, inhibit apoptosis, and prevent inflammation [5][6][7][8][9][10][11][12][13][14][15][16][17][18][25][26][27][28], thereby protecting against cerebral ischemic injury. Over the past few years, the Dan-Hong injection and its ingredients have been widely studied in clinical and basic research [30,[46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…The compatibility of these three active ingredients with hydroxysafflor yellow A (HSYA) in C. tinctorius (Honghua in Chinese) has a better therapeutic effect on cerebral ischemia [2][3][4]. SAA can scavenge free oxygen radicals [5,6] and has a protective effect on cell damage caused by oxidative stress [7,8]. SAB not only has strong antioxidant effects [9][10][11][12][13], but it can also inhibit apoptosis [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%